Problems Encountered by Bachelor’s Level Students in Reading English Texts - Bhandari, Bhimlal (Kalika Journal of Multidisciplinary Research, 2023)
Reading textbooks is challenging as our school-level courses do not teach students how to improve their reading comprehension abilities. They simply memorize the word meaning and question-answers. Also, they have no idea in improving their reading skills. Reading comprehension is still crucial for their academic and personal success but it is being ignored which motivated me to research this issue. This study aimed to explore reading problems encountered by bachelor-level students in English texts. I selected four students studying compulsory English at the bachelor level as the participants purposively from two constituent campuses of TU in Rupandehi. I adopted the phenomenological research method and in-depth interviews as major research tools for collecting information using the thematic analysis technique. None of the previous research is expressive and specific on this issue so, I intend to explore it. This paper reveals students' limited and unfamiliar vocabulary, lengthy texts, unfamiliar and uninteresting text, lack of inference skills, problems with reading fluency, lack of background knowledge about the text, inadequate intensive reading practices, lack of exposure to printed materials, complex sentence structure, and lack of reading habit as problems in understanding of English texts. Hence, it may contribute to enhancing the problems that bachelor-level students face in reading English texts.